The Great Acceleration of fragrances and PAHs archived in an ice core from Elbrus, Caucasus - Vecchiato M.; Gambaro A.; Kehrwald N. M.; Ginot P.; Kutuzov S.; Mikhalenko V.; Barbante C. (Scientific Reports, 2020)
The Great Acceleration of the anthropogenic impact on the Earth system is marked by the ubiquitous distribution of anthropogenic materials throughout the global environment, including technofossils, radionuclides and the exponential increases of methane and carbon dioxide concentrations. However, personal care products as direct tracers of human domestic habits are often overlooked. Here, we present the first research combining fragrances, as novel personal care products, and polycyclic aromatic hydrocarbons (PAHs) as combustion and industrial markers, across the onset of the Great Acceleration in the Elbrus, Caucasus, ice core. This archive extends from the 1930s to 2005, spanning the profound changes in the relationship between humans and the environment during the twentieth century. Concentrations of both fragrances and PAHs rose throughout the considered period, reflecting the development of the Anthropocene. However, within this rising trend, remarkable decreases of the tracers track the major socioeconomic crises that occurred in Eastern Europe during the second half of the twentieth century.